Peran Kepala Sekolah Sebagai Educator dalam Meningkatkan Kompetensi Teknologi Informasi dan Komunikasi - Saipul Annur; Maryamah Maryamah; Melysa Ristianti (Studia Manageria, 2021)
This research is a research on the role of school principals in improving the competence of Information and Communication Technology teachers which will discuss how the role of principals in improving teacher ICT competencies, how the competence of teachers' ICT and supporting and inhibiting factors in increasing Information Technology competence Teacher communication at SMP Negeri 10 Palembang. The method used in this study uses a qualitative type, and a phenomenological approach. Data research techniques use observation, interviews and documentation through data analysis. In validating the data found in the research field the results use source triangulation and technical triangulation. The research results: first The role of the head schools as educators in improving teacher ICT competence are implementing strategies such as holding training, creating a conducive work climate such as providing ICT facilities, always reminding teachers of the importance of ICT in the present and providing motivation in the form of praise and reprimands. Second, the ICT competence of teachers includes computers, the use of software based on the child's condition, the ability of the teacher, software that is practical, simple, efficient, and multifunctional and applies techniques online and offline. Third, supporting factors include teachers' awareness of learning, adequate equipment, and teacher educational background. Barring factors include the limited capacity caused and the budget for ICT training that has not been included in the school budget at the beginning of the year